Decision analysis on sustainable value: Comparison of the London and Taiwan markets for product integration of family security services and residential fire insurance - Jen-Chieh Lee; Tyrone T. Lin (Journal of Risk and Financial Management, 2020)
This paper explores a decision analysis on product integration of family security services and residential fire insurance in the London and Taiwan markets by using the proposed mathematical models for counting sustainable value. This paper shows the five main different results between London and Taiwan markets with ten different parameters of the family security market, to find out the optimal number of family security integrated services for each security company in London. The improvement of the risk aversion effect based on risk and financial management will enhance the market share of the private security industries in the London and Taiwan markets. The results of this research can serve as a reference for the decision-making of private security industries on product integration under sustainable value consideration. The research findings highlight the potential benefits for both the private security industry and the insurance industry in their design and negotiation for product integration to improve both of business operation and achieve corporate social responsibility goals to match the sustainability in the future.
Keywords: 330; sustainability; decision analysis; family security services; residential fire insurance; risk aversion